Assessment of maternal health and behavior during pregnancy in the HEALthy Brain and Child Development Study: Rationale and approach - Kelly K. Gurka; Heather H. Burris; Lucia Ciciolla; Claire D. Coles; Suena H. Massey; Sharlene Newman; Vidya Rajagopalan; Lynne M. Smith; Anna Zilverstand; Gretchen Bandoli (Developmental Cognitive Neuroscience)
The Healthy Brain and Child Development (HBCD) Study, a multi-site, prospective, longitudinal cohort study, will examine human brain, cognitive, behavioral, social, and emotional development beginning prenatally and planned through early childhood. Prenatal exposures, including substances of abuse, impact fetal development and have effects across the life course. During the development of the HBCD Study, the Pregnancy Exposures, Including Substances Workgroup (WG-PRG) was charged with characterizing maternal health and behavior during pregnancy into the childhood years. Maternal physical and mental health, including substance use, and pregnancy and birth complications and outcomes were prioritized. Pregnancy, chronic and acute health conditions, family mental health, and healthcare utilization were assessed using existing and novel measures. Maternal mental health was assessed with the Edinburgh Postpartum Depression Scale, select items in the DSM-5 Self-Rated Level-1 and −2 Cross-Cutting Symptom Measures, and the National Stressful Events Survey-PTSD Short Scale. Finally, participants reported lifetime, recent, and current use of substances using a modified-ASSIST during pregnancy and postpartum. Quantities and frequencies of reported substances were collected for select periods prior to and during pregnancy through an interview (or web application) using the timeline-followback method. HBCD will advance our understanding of the impact of the intrauterine environment on early development.